2015
DOI: 10.1187/cbe.15-02-0043
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacology-Based Enrichment Program for Undergraduates Promotes Interest in Science

Abstract: The authors examined the effect of an intervention (a Summer minicourse and a Fall research course) that was designed to support students' science motivation. Undergraduates improved their knowledge of biology and chemistry concepts, reported high levels of science motivation, and were likely to major in a biological, chemical, or biomedical field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
0
13
0
3
Order By: Relevance
“…Godin and colleagues state that active learning is crucial to students' learning. [16] This pilot study revealed an important finding for educators to consider before planning and conducting a similar learning activity. While the majority of students felt like this was a valuable learning activity, 25.2% responded negatively and neutrally.…”
Section: Discussionmentioning
confidence: 99%
“…Godin and colleagues state that active learning is crucial to students' learning. [16] This pilot study revealed an important finding for educators to consider before planning and conducting a similar learning activity. While the majority of students felt like this was a valuable learning activity, 25.2% responded negatively and neutrally.…”
Section: Discussionmentioning
confidence: 99%
“…These training should be based on student's interests. Because students need to be interested in the subject to succeed in their research . From this point of view, the introduction of skills examination should have been effective.…”
Section: Resultsmentioning
confidence: 99%
“…It is not practical for undergraduates to manage various subjects, experimental methods, and computing methods simultaneously in a limited time period . Third, scientific training should be based on the student's interests . There is a strong agreement among the faculty that students need to be interested in the subject matter to successfully carry out their research .…”
Section: Discussionmentioning
confidence: 99%